From City to Sea : Integrated Management of Litter and Plastics and Their Effects on Waterways - A Guide for Municipalities - World Bank (World Bank, Washington, DC, 2021)
This Guide for Municipalities is intended for use by municipal officers and service providers concerned with: (a) policies and programs that influence waste generation and management; (b) the urban environment in which litter is generated, accumulated, and transported; and (c) the waterways they affect, this includes those in charge of policy, municipal planning, urban planning, public works, and solid waste management. The guide was created to help municipal decision makers, service providers, and municipal planners understand the potentially critical consequences of litter in their cities and develop comprehensive, interdisciplinary approaches to managing litter flows. It introduces an array of management measures and describes when they would be appropriate based on local circumstances. To strengthen the case for taking an integrated litter management approach, it provides background information on the social and environmental challenges posed by litter and how these have been tackled in some cities.